Tourism Destination Benchmarking Analysis - Zlatković, Matea (European Journal of Multidisciplinary Studies, 2016)
Modern society is characterized by constant changes that are rapidly taking place and that are difficult to follow. Management of the company is forced to constantly adapt to changes, to systematically and continuously measures and compares their performance with business results of its competitors. A key condition for survival in the market is to achieve quality. Consequently, it is necessary to estimate their own competitive position and meet with examples of best practice in their own field of work, with the aim of an independent perspective for future development. Benchmarking is the process of defining own areas of business and the identification and understanding of business activities its competitors, in order to determine their own advantages and disadvantages. The objective of the company is to implement the perceived advantages of competitors in its business activities and thereby achieve a better market position. The results of the best practice analysis for the chosen destination indicate the direction which this destination should follow through creative copying an already successful and proven management and marketing models.